PENGARUH KINERJA KEUANGAN DAN OPERASIONAL TERHADAP RETURN SAHAM - Raihan Bahy Rizqullah, (2023)
Stock return is the rate of return on profits generated on investment activities carried out by investors. The purpose of this study is to test and empirically prove the effect of financial and operational performance on stock returns. The population of this study are manufacturing companies that have been listed on the Indonesia Stock Exchange in 2017-2020. The sample of this study consisted of 26 companies and used purposive sampling method. Data analysis was performed using multiple linear regression with STATA software version 14. The results obtained in this study concluded that the debt to equity ratio had a significant negative effect on stock returns and Net Profit Margin is significant positive effect on stock returns. Return on equity, sales growth, and operating cost have no effect on stock returns.